Medical students’ perception of the learning environment at King Saud University Medical College, Saudi Arabia, using DREEM Inventory - Soliman, Mona M (Adv Med Educ Pract, 2017)
BACKGROUND: The students’ perception of the learning environment is an important aspect for evaluation and improvement of the educational program. The College of Medicine at King Saud University (KSU) reformed its curriculum in 2009 from a traditional to a system-oriented hybrid curriculum. OBJECTIVE: The objective of the present study was to determine the perception of the second batch (reformed curriculum) of medical graduates about the educational environment at the College of Medicine, KSU, using the Dundee Ready Education Environment Measure (DREEM) scale. METHODS: The fifth year medical students were asked to evaluate the educational program after graduation in May 2014. The questionnaire was distributed to the graduate students electronically. The DREEM questionnaire consisted of 50 items based on Likert’s scale; and five domains, namely, students’ perceptions of learning, perceptions of teachers, academic self-perceptions, perceptions of atmosphere, and social self-perceptions. Data were analyzed using SPSS. RESULTS: A total of 62 students participated in the study. The score for students’ perception of learning among medical students ranged from 2.93 to 3.64 (overall mean score: 40.17). The score for students’ perception of teachers ranged from 2.85 to 4.01 (overall mean score: 33.35). The score for students’ academic self-perceptions ranged from 3.15 to 4.06 (overall mean score: 28.4). The score for students’ perception of atmosphere ranged from 2.27 to 3.91 (overall mean score: 41.32). The score for students’ social self-perceptions ranged from 2.85 to 4.33 (overall mean score: 24.33). The general perceptions of the students in all five sub-scales were positive. CONCLUSION: The overall student’s perception about the educational environment was satisfactory. This study was important to evaluate the students’ perception of the learning environment among medical graduates of the reformed curriculum and provided guidance on areas of improvement in the curriculum.